Clinical and Laboratory Improvement in Hyperadrenergic Postural Orthostatic Tachycardia Syndrome (POTS) after COVID-19 Infection. (23rd August 2021) - Ocher, Rebecca A.; Padilla, Erika; Hsu, Jonathan C.; Taub, Pam R.
Abstract : A 32-year-old woman with a history of symptomatic supraventricular tachycardia, inappropriate sinus tachycardia, and hyperadrenergic POTS was treated with ivabradine and metoprolol. She then presented with bradycardia and Mobitz II second-degree AV block on event monitoring six weeks after COVID-19 infection. Her post-viral workup revealed normalization of catecholamine levels and significant symptomatic improvement in heart rate. To the authors' knowledge, this is the first reported case of improvement in POTS after COVID-19 infection. As our understanding of COVID-19 continues to improve, it will be vital to better understand the impact of COVID-19 dysautonomia on cardiac patients.